Numerical assessment of the risk of GERD break on the downstream countries - Ahmed M. Elbelasy; Abdel Hamed M. Khater; Eid H. Hassan; Amir S. Ibrahim (Applied Water Science, 2024)
Abstract The potential effects of Grand Ethiopian Renaissance Dam (GERD) failure on the downstream countries were numerically assessed. Flow discharge reaching Lake Nasser and the corresponding water levels were determined, and the inundated areas were defined as a result of GERD failure. High-resolution digital elevation model was developed with 2670-km length starting from GERD till Aswan High Dam. GERD’s reservoir, urban, and rural lands downstream of the GERD were presented using a numerical model. The modeled areas included parts of Ethiopia, Sudan, and Egypt, not to mention Toshka Spillway. The model areas were not divided into parts because of calculating the water levels at the existence of intermediate dams as model outputs. In case possible failure of GERD, Roseires and Sennar dams could collapse. Meanwhile, Merowe dam can sustain with the operation of its emergency spillway. Wave height reaches 100-m downstream of the GERD and 64-m and 31-m downstream of the Roseires and Merowe dams, respectively.